2020
DOI: 10.1186/s12877-020-1439-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urine and mixed incontinence on long-term care preference: a vignette-survey study of community-dwelling older adults

Abstract: Background: In view of population aging, a better knowledge of factors influencing the type of long-term care (LTC) among older adults is necessary. Previous studies reported a close relationship between incontinence and institutionalization, but little is known on opinions of older citizens regarding the most appropriate place of care. This study aimed at evaluating the impact of urine and/or fecal incontinence on preferences of communitydwelling older citizens. Methods:We derived data from the Lausanne cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Twenty‐nine studies out of 35 studies explored the impact of age on willingness of older people to engage with long‐term care services in 110,119 participants. Fifteen studies found a significant association between age and the willingness of older people to engage with long‐term care services (Carvalho et al, 2020; Hajek et al, 2017; Han et al, 2017; Kim & Kim, 2004; Liao, 2019; McCormick et al, 2002; Qian et al, 2018; Rodríguez, 2014; Shi & Hu, 2020; Sugisawa et al, 2020; Wang et al, 2004, 2020; Wei & Zhang, 2020; Xu et al, 2018; Zeng et al, 2019). And 10 studies found that the younger older people were likely to choose formal care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐nine studies out of 35 studies explored the impact of age on willingness of older people to engage with long‐term care services in 110,119 participants. Fifteen studies found a significant association between age and the willingness of older people to engage with long‐term care services (Carvalho et al, 2020; Hajek et al, 2017; Han et al, 2017; Kim & Kim, 2004; Liao, 2019; McCormick et al, 2002; Qian et al, 2018; Rodríguez, 2014; Shi & Hu, 2020; Sugisawa et al, 2020; Wang et al, 2004, 2020; Wei & Zhang, 2020; Xu et al, 2018; Zeng et al, 2019). And 10 studies found that the younger older people were likely to choose formal care.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies, with 58, 894 participants in total, reported the relationship between living arrangements and the willingness of older people to engage with long‐term care services. Thirteen studies out of the 17 studies found a significant association between living arrangements and willingness to choose long‐term care services of older people (Carvalho et al, 2020; Hajek et al, 2017; Han et al, 2017; Wang & Wu, 2008; Qian et al, 2017; Li, Yue, & Bi, 2015; Li, Fu, et al, 2015; Peng, 2017; Rodríguez, 2014; Shi & Hu, 2020; Wang et al, 2020; Liao, 2019; Wang et al, 2017; Zhang et al, 2017). And older people who lived with spouse or children were more likely to opt for informal long‐term care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 Among the disability and social characteristics displayed in the vignettes, incontinence was a key factor explaining the perception of a need for institutionalization. 24 In a longitudinal study applying Andersen’s Behavioural Model of Health Services Use, incident utilization of formal home care appeared to be largely determined by need factors such as chronic health conditions and functional limitations, as compared with predisposing factors (e.g. sociodemographic characteristics, beliefs about health services) and enabling factors (e.g.…”
Section: What Has It Found?mentioning
confidence: 99%